Dmitri Shostakovich, pianist - Moshevich, Sofia (McGill-Queen's University Press, 2004)
She traces his musical roots, piano studies, repertoire, and concert career through his correspondence with family and friends and his own and his contemporaries' memoirs, using material never before available in English. This biographical narrative is interwoven with analyses of Shoshtakovich's piano and chamber works, demonstrating how he interpreted his own music. For the first time, Shoshtakovich's own recordings are used as primary sources to discover what made his playing unique and to dispel commonly held myths about his style of interpretation. His recorded performances are analysed in detail, specifically his tempos, phrasing, dynamics, pedal, and tonal production. Some unpublished variants of musical texts are included and examples of his interpretations are provided and compared to various editions of his published scores.
Keywords: Shostakovich, Dmitriĭ Dmitrievich, -- 1906-1975.; Chostakovitch, Dmitri Dmitrievitch, -- 1906-1975.; Shostakovich, Dmitriĭ Dmitrievich, -- 1906-1975; Šostakovič, Dmitrij D.; Composers -- Soviet Union -- Biography.; Pianists -- Soviet Union -- Biography.; Compositeurs -- U.R.S.S. -- Biographies.; Pianistes -- U.R.S.S. -- Biographies.; Compositeurs -- URSS -- Biographies.; Pianistes -- URSS -- Biographies.; BIOGRAPHY & AUTOBIOGRAPHY -- Composers & Musicians.; MUSIC -- Musical Instruments -- Piano & Keyboard.; MUSIC -- Printed Music -- Piano & Keyboard Repertoire.; MUSIC -- Genres & Styles -- Classical.; Composers; Pianists; Soviet Union; Klaviermusik; Pianist; Componisten.; Pianisten.; Electronic books.; Biographies; Biographies.